"This isn't your father's police force": Digital evidence in sexual assault investigations. Issue 4 (December 2019) - Dodge, Alexa; Spencer, Dale; Ricciardelli, Rose; Ballucci, Dale
Digital evidence, once regarded as existing only in a portion of criminal cases, in our digitized world commonly appears within all crime categories and is a factor in many (or arguably most) cases of sexual assault. In this article, we draw from 70 interviews with sex crime investigators from across Canada to demonstrate that the infusion of digital evidence into sexual assault investigations results in new opportunities and challenges for police and both negative and positive impacts on victims' experiences within the criminal justice system. We show that while digital evidence certainly provides more opportunities for documenting the context and content of acts of sexual assault, police perceive this evidence as a double-edged sword that provides both more evidence and new challenges for police and victims. While officers express that digital evidence may provide more conclusive proof in the notoriously difficult pursuit of proving sexual assault charges, they are also concerned that this evidence provides new challenges for already overburdened sex crime units and makes cases more lengthy and invasive for victims. This article contributes to emerging research on the challenges of policing in the digital age and to the dearth of research on the potential and pitfalls of digital evidence in sexual assault investigations.